Short startup, batteryless, self‐starting thermal energy harvesting chip working in full clock cycle - Arun Kumar Sinha; Marcio Cherem Schneider (IET Circuits, Devices and Systems)
The Internet of Things paradigm considers the deployment in the environment of a profusion of heterogeneous sensor nodes, connected in a complex network, and autonomously powered. Energy harvesting is the common proposed solution to supply such sensors, and many different sources such as light, mechanical vibrations, temperature differences can be considered individually or in combination. Specifically, a thermoelectric generator (TEG), taking advantage of the Seebeck effect, is able to harvest electrical power from a temperature gradient of a few degrees. This study presents a chip fabricated in 130 nm CMOS technology, designed to convert a typical 50 mV output from a TEG into 1 V. The batteryless design utilises both halves of a 50% duty cycle clock. Measurements have been performed by using a TEG, and an equivalent TEG model, i.e. voltage source (50 mV–200 mV) with a series resistance of 5 Ω. The result shows that the proposed prototype can extract 60% (at 50 mV) to 65% (at 200 mV) of the total available power. The energy harvester can self‐start at 50 mV with a 2.8 ms startup time, which is a significant improvement over the past work.